Integrated postharvest management of anthracnose in dragon fruits using plant extracts - Bordoh, Paa Kwesi (2018)
Integrated Postharvest Management of Anthracnose in Dragon Fruits Using Plant Extracts The study was conducted to develop an environmentally, biodegradable, non-toxic and sustainable bio-fungicide using the formulation where each plant crude extract (ginger, turmeric and “dukung anak”) at different concentrations were incorporated separately with 10% gum Arabic (GA). The formulation was assessed against a wide range of parameters such as disease incidence (DI) and severity (DS) as well as postharvest quality (physicochemical and nutritional) on dragon fruits during storage at 11±20C, 80% RH for up to 28 days. Additionally, the study also investigated a diagnostic tool, thus Loop-mediated isothermal amplification (LAMP), for early detection of anthracnose in dragon fruits caused by Colletotrichum gloeosporioides Penz during postharvest storage. Prior to the formulation, the antifungal effect of each plant extract alone was evaluated in vitro (against C. gloeosporioides ) at concentrations (2.5 mg/ml, 5 mg/ml, 7.5 mg/ml and 10 mg/ml) and in vivo (on the fruits to control anthracnose) at concentration (5 mg/ml, 10 mg/ml and 15 mg/ml). In vitro antifungal activity of plants extracts alone showed that all plant extracts showed significant antifungal activity against C. gloeosporioides that causes anthracnose in dragon fruit. This was evident in inhibition of mycelial growth and conidial germination, which translated to morphological damage such as distortion and shrivelling in the fungal hyphae during scanning electron microscopy (SEM) studies result. Ginger crude extracts at 10 mg/ml showed a promising result in terms of suppressing mycelial growth (88.48%) and conidial germination (87.5%) which was comparable to commercial fungicide (Mancozeb) at 2 mg/ml (80.45%). In the in vivo study, where dragon fruits were coated (treated) with only plant extracts by dipping, fruits treated at 15 mg/ml irrespective of the crude extracts experienced severe disease incidence due to phytotoxicity. However, DI and DS was significantly low in dukung anak-treated fruits irrespective of the concentration used. Postharvest anthracnose caused by C. gloeosporioides and its severity was signficantly low in dukung anak-treated fruits at 10 mg/ml which was not different in fruits treated with 10 mg/ml of turmeric crude extracts after 28 days of cold storage. The antifungal activity was due to the presence of bioactive compounds gingerol, curcumin and some alkaloids in ginger, turmeric and dukung anak which resulted in electrolye leakage from fungal cell wall contributing to direct control of anthracnose. Whiles dukung anak extract controlled anthracnose and its severity at 10 mg/ml, DI was more pronounced in ginger-treated fruits even at 5 mg/ml due to phytotoxicity. Overall, disease incidence was highest especially at 15 mg/ml irrespective of plant extract used. Additionally, the external appearance of treated fruits at 10 mg/ml and 15 mg/ml of extracts alone (irrespective of the type of plant used) negatively affected customers appeal and preference due to compromised original smell and colour of the fruit. To overcome this problem, a formulation compromised of each plant crude extracts especially at higher concentrations (10 mg/ml and 15 mg/ml) and at a lower concentration (5 mg/ml) were incorporated with 10%GA to develop a alternative non-chemical approach that can enhance the efficacy of each plant extract against anthracnose whilst improving other postharvest quality of fruits. Fruits treated with a composite coating of 10%GA+10 mg/ml turmeric crude extracts significantly reduced anthracnose and its severity by about 94% compared to controls. This was not different in fruits treated with 10%GA+15 mg/ml ginger extract after 28 days of storage. For a rapid detection of postharvest anthracnose caused by C. gloeosporioides, LAMP, a diagnostic tool showed that composite coating of 10%GA+5 mg/ml of turmeric markedly reduced the amount of fungal DNA isolated from infested fruits compared to controls. A clear indication that Lamp can be used for detection of anthracnose during postharvest storage. Generally, respiration rate and ethylene production were significantly lower in fruits coated with 10%GA plus either 10mg/ml or 5 mg/ml of ginger crude extracts even though it was markedly low in fruits coated with 10%GA+10 mg/ml of the either turmeric or dukung anak crude extracts. In this study, fruit treated coated with 10%GA+10 mg/ml of any crude extracts especially turmeric crude extract showed the greatest ﬁrmness, reduced water loss, delayed colour development, lowered the levels of TSS and maintained a high TA after 21 to 28 days of storage. Furthermore, an composite coating of 10%GA+10 mg/ml of turmeric crude extract helped to maintain higher total antioxidant and nutritional activity in dragon fruits due to the presence of high ascorbic acid content and total phenolic compounds. Similarly, sensory evaluation results proved the effectiveness of 10%GA+10 mg/ml of turmeric crude extract composite coating by maintaining the overall quality of dragon fruits. These findings suggest that 10%GA+10 mg/ml of turmeric crude extracts can be used for extending the storage life of dragon fruits for up to 28 days. Additionally, this study proposes LAMP as a promising diagnostic tool for early detection of postharvest anthracnose in dragon fruits and other tropical fruits during regular checks in transits (sea transports) or at packing houses. By doing so, the onset of postharvest anthracnose could be detected and immediate steps taken to control the disease.